PERANCANGAN BUKU EDUKASI MENGENAI ILUSTRASI MENJAGA GIZI SEIMBANG SEBAGAI MEDIA INFORMASI - Putri, Werdany Ayudya; Nisa, Diana Aqidatun; Masnuna, Masnuna (Universitas Negeri Makassar, 2024)
The problem of eating is closely related to the development of the child itself. Some signs in children who are malnourished can be seen from insignificant weight loss, difficulty concentrating which can occur due to anemia or a lack of vitamin A, pale skin or pale lip color, and easily tired and lethargic because the body is not carrying out its functions properly. Indonesia is one of the countries in the world that still requires special attention in terms of balanced nutrition. Consumption of food and nutrition makes a very large contribution to the nutritional status and health of children. Food also affects brain development. Lack of food containing the nutrients needed in a prolonged period can have an adverse effect on children's growth and result in changes in brain metabolism. The use of methods in conducting this research using Qualitative methods and Quantitative Methods. The qualitative method uses an interview approach, while the quantitative method uses a questionnaire approach. The approach taken to collect data resulted in a design concept with the keyword